Arquivo Histórico Municipal Juarez Miguel Illa Font (1980-2020): cultura histórica e crítica ao "erechinense cordial" - Trizoto, Henrique Antônio (2026)
The construction of the History of the Erechim Colony up to the present day is permeated by a narrative that exalts the figure of the immigrant and portrays him as a pioneer, while not infrequently the presence of ethnic groups not originating from Europe (Black, caboclo, and Indigenous peoples) is silenced. In this sense, we seek to analyze the Permanent Collection of the Juarez Miguel Illa Font Municipal Historical Archive (AHMJMIF) of Erechim and the trajectory (1980–2020) that consolidated it as a cultural space which, in theory, preserves (or would preserve) the narrative of the city’s foundation, colonization, and socio-political structuring, along with its possible silences. We will investigate how the collections that constitute it give rise both to more traditional and to renewed historical productions, based on the relationship established between researchers and documents that address local history. In addition to analyzing the works considered “classics” regarding the municipality’s historical narrative, the methodological path includes the discussion of contemporary works on local history available in the AHMJMIF collection and on academic platforms such as the Digital Library of Theses and Dissertations (BDTD) of Capes, Google Scholar, and the institutional repositories of UPF and UFFS. The structuring of the thesis is permeated by the understanding of the concepts of official narrative (Hobsbawm, 1984), cordiality (Holanda, 1995), national identity (Anderson, 2005; Schwarcz, 1993), and heroic past (Albuquerque Junior, 2007). For the purpose of validating the thesis, twenty dissertations and two theses that were built with documents from the AHMJMIF collection and are available on the platforms of UFFS, UPF, PUC, and the Capes Digital Library of Theses and Dissertations will be analyzed. This allows us to affirm that the official narrative still remains consolidated in these productions, but it already presents cracks, questions, and signs that this cordiality,which varnishes and protects the status quo, is now being analyzed in light of its false affability that generates exclusion, silencing, authoritarianism, and veiled violence.